Pelaksanaan pembelajaran menyeronokkan dalam pengajaran dan pembelajaran Bahasa Melayu - Jamian, Abdul Rasid; Ismail, Hasmah (Fakulti Pendidikan, Universiti Kebangsaan Malaysia, 2013)
This study is carried out to identify the readiness of teachers teaching Bahasa Melayu in applying fun ways, their perception and its appropriateness in teaching Bahasa Melayu in fun learning. In order to improve the performance of teaching and learning the subject. This study is conducted on 92 teachers teaching Malay Language from 8 schools in Pasir Putih Zone in Pasir Gudang, Johor. This research based on descriptive with questionnaire. The findings are analysed using the descriptive statistics which covers the distribution frequency, percentage, mean and standard deviation. The findings shows teachers are being positive and having high confidence towards the use and the appropriateness of fun way learning in the teaching and learning Malay Language. They also agreed that the use of multimedia could create a fun way of learning. However, Bahasa Melayu subject teachers are still lacking of the use of teaching aids. As a result, they tend to use the teaching technique which is based on the teacher or student talents instead of using printed materials, visual aids and multimedia software to create fun learning habit.